If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(-1-6x)=34
We move all terms to the left:
2(-1-6x)-(34)=0
We add all the numbers together, and all the variables
2(-6x-1)-34=0
We multiply parentheses
-12x-2-34=0
We add all the numbers together, and all the variables
-12x-36=0
We move all terms containing x to the left, all other terms to the right
-12x=36
x=36/-12
x=-3
| –6=–3z | | -7b=-10b-18 | | W=g+7 | | 22=v+5 | | x²+6x-10=30 | | -9-2c-2=-11+14c | | M(x)=20x+20 | | -2(1-x)=11 | | 2k+24=22 | | -3r-3=9 | | 147=-v+208 | | p+19=20 | | -4q+10=-10q-10-10 | | –6+2z=–z | | -7-5c=-6c | | 4+16s=-10+12s+2s | | t÷0.3=1.4= | | -y+46=160 | | 6-5g=-8g | | 7.1n+15.11=-7.5n-18.47 | | -19+b=-34 | | 7a+4=3a−20 | | 49=6c–13–4c | | 28-k=7(k-4 | | 2(12-3y)=12 | | 9x^2-64x-320=0 | | t÷0.3=1.4 | | -17d-9=-20d | | -r-4(2r-4)=61 | | 2/3=51/x | | -10-9q=18-11q | | X/460+x/500=4.8 |